2020
DOI: 10.1016/s2468-1253(19)30416-9
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is most frequently detected at an advanced stage. This limits treatment options and contributes to a dismal 5-year survival rate of 3 to 15%. PDAC is relatively uncommon and with current modalities, screening of the asymptomatic adult population is not feasible or recommended. However, screening of individuals in highrisk groups is undertaken. Here we review high-risk groups for PDAC, including individuals with inherited predisposition and patients with pancreatic cystic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
320
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(344 citation statements)
references
References 120 publications
(141 reference statements)
5
320
0
19
Order By: Relevance
“…A previous review investigating the role of pepsinogens in early detection of gastric cancers reported that they had only moderate capacity to detect gastric cancer [173]. Another review on early pancreatic cancer detection highlighted that no single biomarker has yet translated to clinical use and suggested the use of 'robust panels of biomarkers' [9]. This review confirms that more research is required before we have sufficient evidence about biomarkers for upper GI cancers to warrant their adoption into clinical practice.…”
Section: Discussionsupporting
confidence: 57%
“…A previous review investigating the role of pepsinogens in early detection of gastric cancers reported that they had only moderate capacity to detect gastric cancer [173]. Another review on early pancreatic cancer detection highlighted that no single biomarker has yet translated to clinical use and suggested the use of 'robust panels of biomarkers' [9]. This review confirms that more research is required before we have sufficient evidence about biomarkers for upper GI cancers to warrant their adoption into clinical practice.…”
Section: Discussionsupporting
confidence: 57%
“…Pancreatic cancer is one of the most dangerous solid cancers (Kamisawa et al 2016;Pereira et al 2020). The American Cancer Society estimates that 57,600 individuals (30,400 men and 27,200 women) will be diagnosed with pancreatic cancer, and pancreatic cancer will cause approximately 47,050 deaths (24,640 men and 22,410 women) in 2020 (https://www.cancer.org/cancer/pancreatic-cancer/ about/key-statistics.html, accessed on May 11, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis is essential in improving the prognosis of pancreatic cancer, but it is challenging (Singhi et al 2019;Vasen et al 2019;Pereira et al 2020). The Pancreatic Cancer Registry in Japan revealed that the 5-year survival rates of patients with the Union for International Cancer Control stage 0 (high-grade pancreatic intraepithelial neoplasia [PanIN]/ carcinoma in situ [CIS]), stage IA (tumor size < 2 cm with no lymph node metastasis and no distant metastasis), and stage IB (tumor size > 2 cm but no more than 4 cm, with no lymph node metastasis and no distant metastasis) were 85.8%, 68.7%, and 59.7%, respectively, but accounted for only 1.7%, 4.1%, and 6.3%, respectively, in all registered patients (Egawa et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer continues to have a poor 5-year survival rate despite its rising incidence [20,21]. By 2030, it is estimated to become the second leading cause of cancer related deaths [5].…”
Section: Discussionmentioning
confidence: 99%